KEPEMIMPINAN KIAI DALAM PENINGKATAN KUALITAS PENDIDIKAN: Studi Kasus Pondok Pesantren Harisul Khairaat Bumi Hijrah Kota Tidore dan Kepuluan Provinsi Maluku Utara - Andy (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstrak: Kiai's Leadership in Improving the Quality of Education Case Study of Harisul Khairaat Bumi Hijrah Islamic Boarding School, Tidore City and Islands, North Maluku Province This study will answer the problem of the kiai's leadership style and its implications for improving the quality of education in a case study at the Harisul Khairaat Islamic Boarding School in Bumi Hijrah Tidore and the Archipelago of North Maluku Province. This research was conducted with a qualitative approach. Data collection techniques used using observation, interviews, and documentation. The results of this study found that: 1) KH An'aim Fatahna Djabir's leadership style was charismatic leadership; 2) KH An'aim Fatahna Djabir's leadership strategy was to improve the quality of human resources and students through increasing competence and enrolling students in national competitions and local areas, as well as improving facilities and infrastructure, and performance-based strengthening of the vision, mission, and targets. The implications of KH An'aim Fatahna Djabir's leadership are that the KIAI as caregiver involves many people, an effective leader is someone who is able to influence his followers to achieve the vision, mission, goals, and objectives, leadership must be a role model, provide convenience for teachers who want to work, create a comfortable working atmosphere and build student obedience.